Pengaruh Perilaku Proaktif terhadap Keunggulan Bersaing di UMKM Peternak Puyuh Desa Bendowulung Kecamatan Sanankulon Kabupaten Blitar - Eko Adi Susilo; Kasiani Kasiani; Rizki Tri Novianto (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the influence of proactive behavior on competitive advantage in quail breeder MSMEs in Bendowulung Village, Sanankulon District, Blitar Regency. The background of this research is based on the importance of increasing the competitiveness of MSMEs in the livestock sector in order to be able to survive and develop in the midst of increasingly competitive market competition. The research method uses a quantitative approach with data collection techniques through surveys or questionnaires distributed to quail farming MSMEs. The data were analyzed using statistical methods, including validity tests, reliability tests, classical assumption tests, linear regression tests, and hypothesis tests to determine the significance of the influence of proactive behavior on competitive advantage. The results of the study show that proactive behavior has a positive and significant influence on competitive advantage. These findings indicate that the higher the level of proactive behavior of an individual or organization, the greater their ability to innovate, take initiative, and adapt to changing business environments. Thus, proactive behavior is a strategic factor in strengthening the position of quail breeder MSMEs in the market, increasing revenue, and encouraging sustainable business performance. This research contributes to the development of MSME management theory and practical recommendations for business actors and policy makers.